Analisis Stabilitas Dan Alternatif Perkuatan Lereng Dengan Geomat Menggunakan Metode Elemen Hingga - Dendi Yogaswara; Bima Guna Bhakti (Jurnal Konstruksi, 2026)
Landslides are natural disasters that can result in loss of life, property damage, and environmental degradation. One of the key contributing factors is the steepness of the slope. In October 2021, the slope near the Cisumdawu Toll Tunnel experienced several landslides, particularly around the tunnel outlet. This study aims to determine the safety factor values, evaluate the effectiveness of slope angles, and assess reinforcement using geosynthetics (Geomats) at varying slopes of 30°, 38°, and 63°. Slope stability was analyzed using the Bishop method, which provides results close to actual conditions. The analysis was also modeled and verified using GeoStudio Slope/W Student Version software. The safety factor obtained from the manual Bishop method was 2.07, while the GeoStudio analysis yielded 2.064. The slope stability analysis with varying slope angles resulted in different safety factor values: 2.3 at 30°, 1.96 at 38°, and 1.491 at 63°. After applying reinforcement using four layers of Geomat and wire mesh Geomat at the same slope angles, the safety factors improved, with better performance shown by the wire mesh Geomat. At a slope of 1:0.5 (63°), the safety factor was 1.494 with four-layer Geomat and 1.508 with wire mesh Geomat; at 1:1.5 (34°), the values were 2.068 and 2.075 respectively; and at 1:1.7 (30°), they were 2.305 and 2.312. The gentler the slope surface, the more stable the safety factor. The application of Geomats can prevent erosion and facilitate plant vegetation growth, thereby enhancing slope stability.